MODEL PEMBELAJARAN BAHASA INGGRIS BERBASIS KUMON UNTUK MENINGKATKAN KEMAMPUAN READING MAHASISWA - Oktariyani, Oktariyani; Oktariyana, Oktariyana (Lentera: Jurnal Ilmiah Kependidikan, 2020)
Abstract- This study aims to develop and test the effectiveness of a product in the form of a Kumon-based English learning model. This research uses qualitative and quantitative approaches. While the research method used in this study is a research and development method which adopts the theory of Borg and Gall. This research has produced a product in two forms, namely Kumon-based reading learning books and audio. Based on the results of the effectiveness test of the Kumon-based learning model of English, it is proven that there is a significant difference (meaning) between before and after being given the Kumon-based learning model. This can be seen from the results in the significant difference test obtained by mean = 0.220, indicating the difference between the pretest and posttest results, the results of t-count = 9.465, with db = 29 and p-value = 0.224 â‰¥ 0.05, which means that there is a significant difference. Significant between before and after being given the Kumon-based English learning model treatment. So thus the Kumon-based English learning model that has been developed is better than the previous learning model. And based on the table of output descriptions of the N-gain score on the data of the reading ability of the students mentioned above, it shows that the average N-gain score is 58.03%, including in the category "Quite Effective", with a minimum N-gain score of 3.23. % and a maximum N-gain score of 100%. So it can be concluded that the use / application of the English learning model of English based on the Kumon "Effective Enough" can improve students' reading skills.